(untitled) (Journal of Asian Development Studies, 2025)
Adolescence is a crucial developmental stage during which various external influences shape identity formation and self-worth. This study investigates how school climate and peer victimisation jointly influence self-esteem and identity continuity in adolescents, with particular attention to minority youth. Using a sample of 150 adolescents, multiple regression and interaction analyses revealed that a supportive and inclusive school climate was positively associated with stronger identity continuity and healthier self-concept. At the same time, experiences of peer victimisation had a detrimental impact on both self-esteem and identity development. Consistent with prior findings (Bear et al., 2015; Rivas-Drake et al., 2014), the results highlight how a nurturing environment promotes resilience and provides adolescents with a sense of belonging that buffers them against negative social experiences. The findings highlight not only the independent effects of school climate and peer victimisation but also their interactive influence in shaping developmental trajectories. For minority students, who often face ethnic victimisation or discrimination (Benner et al., 2018), these dynamics can be especially pronounced, amplifying risks to psychological and academic adjustment. By situating these results within broader literature on school-based inclusion (Juvonen et al., 2019), the study underscores the importance of cultivating equitable, safe, and inclusive educational settings that can promote resilience, continuity of identity, and overall well-being during a formative life stage.